Circularly polarized activity from two photon excitable europium and samarium chiral bioprobes. Issue 12 (14th March 2023) - Mizzoni, Silvia; Ruggieri, Silvia; Sickinger, Annika; Riobé, François; Guy, Laure; Roux, Margaux; Micouin, Guillaume; Banyasz, Akos; Maury, Olivier; Baguenard, Bruno; Bensalah-Ledoux, Amina; Guy, Stéphan; et al.
Abstract : Circularly polarized luminescence activity from new cationic water soluble Sm(iii ) and Eu(iii ) complexes is triggered by one- and two-photon absorption processes. The Eu(iii ) complex is shown to be an efficient NIR-to-RED probe in cellulo . Abstract : In this contribution, two couples of cationic enantiomeric complexes [( R, R )-[LnL ]Cl and ( S, S )-[LnL ]Cl, with Ln = Sm and Eu and L = N, N ′-bis(2-pyridylmethyl)-1, 2-( R, R or S, S )-cyclohexanediamine functionalized at sp 3 N with the picolinate antennae 2 ] have been synthesized and spectroscopically characterized in polar protic solvents, such as water and methanol. The good sensitization of Sm(iii ) and Eu(iii ) luminescence by the picolinate antenna is documented, upon both a one photon absorption process (at about 330 nm) and a two photon absorption process (at 720 nm). The complexes exhibit good CPL activity, in particular for the magnetic dipole (MD) allowed transitions, which are the 4 G5/2 → 6 H5/2 (564 nm) of Sm(iii ) and the 5 D0 → 7 F1 (593 nm) of Eu(iii ). Both complexes are highly stable in aqueous solution (log K = 20.13 for the EuL species chosen as the representative) and only one main species is present at physiological pH (7.4). Among the three possible isomeric complexes, DFT calculations on the Y(iii ) counterpart reveal the highest stability of the C 1 -symmetric cis –O, O–N, N isomer, in agreement with the presence of only one Eu(iii ) emitting species in solution. Furthermore, one solvent molecule is bound to the metal ions, giving rise to 9-fold coordinated complexes. Preliminary biphotonic imaging experiments on the ( S, S )-[EuL ]Cl complex reveal that it can be easily internalized in two different cell lines (namely 293T cancer cells and THP-1 macrophages) with perinuclear diffuse localisation in the cytosol. Both Sm(iii ) and Eu(iii ) complexes can be considered promising candidates as NIR-to-RED in cellulo chiroptical bioprobes and a possible extension to the in vivo experiment will be further investigated.